Measuring the benefits of insect-based food among Chinese consumers: a mixed-method approach - Liu, Yunyao; Kim, Seongseop; Choe, Jacey Ja Young; Wang, Shengpeng (Frontiers in Sustainable Food Systems, 2025)
PurposeThis study aimed to use a mixed-method approach to develop a comprehensive tool to measure the perceived benefits of consuming insect-based food.Design/methodology/approachIn the first step, the construct and item generation was developed by literature review and in-depth interviews, and 67 initial items were generated. In the second step, 41 items were evaluated and refined through expert reviews. The third step involved a pretest with 45 locals, followed by an exploratory factor analysis to validate the scale. In the fourth step, a pilot test was conducted with 200 residents to refine the scale items. Finally, data were collected from 1,089 Chinese consumers to further validate the reliability and validity of the scale.FindingsThe results showed that insect-based food consumption benefits consisted of six dimensions (health, nutritional, taste and flavor, cultural, financial, and environmental value benefits). The overall structure demonstrated satisfactory reliability and validity. The perceived benefits of insect-based food influence customers' attitudes, consumption values, and consumption intentions differently based on gender, age, and education level.Research implicationsBy exploring the benefits of consuming insect-based food, this study provides a specific measurement tool to help promote insect-based food consumption, enriching the existing literature in the food fields.OriginalityTo the best of the authors' knowledge, this is the first study to develop a measurement tool to measure the benefits of eating insect-based foods from a consumer perspective.